The uses of defeat: From territorial mutilation to the rescue of the glorious past in central Andean countries - Solari Pita, Mirko (2020)
Andean historiographies are impregnated with an extended idea of territorial mutilation, which tends to affect the nation’s image. As well as evoking a social imagery of real and symbolic loss of its original greatness. This kind of “myth of origin” hides the absence of inclusive national projects in Ecuador, Peru and Bolivia. The notion of loss seems to constitute an attribute, since far from debilitating the imaginary of the nation, tends to reinforce it and to lend it legitimacy. In pre-Hispanic times, the societies of these three countries were historically articulated. Their logics differed from that of the colonial cartography, of the nineteenth-century States affairs, and of the Creole elites. At present, the territorial factor does not play a pivotal role in the representations of legitimacy of the countries of the central Andean region. However, the stamp of the territorial mutilation has significantly marked the identities of their social actors.